Security Agencies and the Management of Media’s Early Warning Report - BODUNDE, David Oluwafemi; AFOLABI, Muyiwa B. (Nigerian Journal of Peace, Development & Humanitarian Affairs, 2022)
One of the sustainable factors that keep a nation from impending danger is early warning. In the world of information, the media assists the security agents to gather information through information-sharing and dissemination to keep the world out of impending dangers. Both the press and security agencies need each other in the process of gathering important information that touches on the political security of a nation. With the wave of terrorism, nuclear proliferation, insurgency and environmental hazard which pose threat to national security, the world needs quick information on escalating developments, be they slow and gradual or quick and sudden, to react timely and effectively, if possible, leaving them time to employ intelligence and other non-coercive or military preventive measures. Since these measures require information, therefore, the press and security roles are interdependent, hence an attempt by this paper to highlight the importance roles of security agencies and the media in early warning. It adopts persuasive communication theory and unified theory of acceptance and use of technology and derives its data from observation and desk research. The paper concludes that, if early warning signal is well reported by the media and intelligently processed by the security agencies, it will help a nation to combat crimes, promote peace and be ready to face future threats.